Pilot randomised controlled trial on the feasibility and intervention satisfaction with an educational group programme for adults with attention deficit hyperactivity disorder and their caregivers - Tatiana Skliarova; Rolf W. Gråwe; Jonas Vaag; Arthur Mandahl; Inger Kolltveit; Ina Løvås; Terje Torgersen; Mariela L. Lara-Cabrera (BMC Psychiatry)
Abstract Background This pilot randomised controlled trial (RCT) study presents a patient-centred educational group programme collaboratively developed with user representatives and caregivers from two organisations and health personnel from a community mental health centre (CMHC). The objectives were to investigate the feasibility of the psychoeducational programme and the satisfaction of outpatients and caregivers with programme participation. This RCT explored the potential benefits of this innovative psychoeducational programme for adults recently diagnosed with attention deficit hyperactivity disorder (ADHD). Methods This pilot study employed a two-arm RCT design and recruited 60 outpatients from a Norwegian CMHC. The CMHC clinicians offered the intervention group (IG) participants a two-session, patient-centred, peer-cofacilitated programme along with the standard treatment. The control group (CG) received the standard treatment and a 1-h individual informational session during the same period. The recruitment, attendance, and dropout rate indicators were assessed for feasibility. Acceptability was assessed via the Client Satisfaction Questionnaire four-item scale (CSQ-4) and a three-item scale evaluating patient satisfaction with the information provided about ADHD. In addition, four patient-reported outcome measures (PROMs) were applied: one scale to assess self-efficacy, two to assess ADHD symptoms, and one for quality of life. The statistical analysis applied intention-to-treat (ITT) and per-protocol (PP) analyses. Results In total, 56 outpatients were divided into the IG (n = 30) or CG (n = 26), and the recruitment rate was 93.3%, with a dropout rate of 16%. The attendance rate was 92%, and the retention rates for the IG and CG were 56.6% and 76.9%, respectively. Concerning intervention satisfaction, the ITT analysis conducted using a linear mixed model revealed statistical improvements in satisfaction, with the scale measuring satisfaction with the information and the CSQ-4 scale. In addition, caregivers expressed high satisfaction with the programme, as measured by the CSQ-4 scale. Regarding PROMs, the ITT and PP analyses yielded mixed findings. Conclusion Preliminary evidence indicates that a two-session, patient-centred, peer-cofacilitated psychoeducational programme is feasible and well-received, with high ratings for satisfaction from outpatients and caregivers. Cliniclatrials.gov Identifier NCT03547843, 27/01/2022.